Śląskie libri ordinarii z pierwszej połowy XV w. Stan badań nad typem rękopisów, przyczyny powstawania, katalog - Szukiel, Piotr (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny)
The paper discusses the current state of research on medieval European libri ordinarii, focusing on those written in the 1st half of the 15th century in Silesia. Within the present work, the circumstances of their introduction were reconstructed and the character of the manuscripts was described; an attempt was also made to show the probable ways through which the ideas of creating manuscripts of this type spread to Silesia from neighbouring countries. Finally, the relationship between the appearance of venerating church feasts in the triplex rite in the liturgical practice of the churches in the diocese of Wrocław in the 1st half of 15th century and the popularisation of libri ordinarii was examined. The above disquisition is complemented with a catalogue of the preserved libri ordinarii from the diocese of Wrocław.
Keywords: liturgy; Middle Ages; diocese of Wrocław; diocesian synods in Middle Ages; canon regular